Dual mode selective detection and differentiation of TNT from other nitroaromatic compounds - Patil, Goudappagouda; Dongre, Sangram D.; Das, Tamal; Babu, Sukumaran Santhosh (Journal of Materials Chemistry A, 2020)
Selective detection of explosives, especially TNT, is a highly desirable area of research and various explosives detection devices including fluorescent sensors are already in place. However, multi-mode sensors will be more useful and reliable than conventional fluorescent ``Turn Off'' sensors. One of the challenges is the development of selective sensors to prevent illegal transport of commonly used explosive TNT through on-the-spot analysis. In this context, we report a fluorescent polymer-based selective detection of TNT using both fluorometric and colorimetric signals. In addition, colorimetric differentiation of TNT from other nitroaromatic compounds is made possible by complexing with various amines. Even though many other sensors are available for TNT, the current demonstration is unique in terms of selectivity, sensitivity, reliability, portability, and rapidity of results. The as-developed explosive detection kit can be useful in both civilian and military operations to trace the illegal transport of TNT as well as for post-explosion analysis.

Isomer effect on energy storage of π-extended S-shaped double[6]heterohelicene - Kumar, Viksit; Bharathkumar, H. J.; Dongre, Sangram D.; Gonnade, Rajesh; Krishnamoorthy, Kothandam; Babu, Sukumaran Santhosh (Angewandte chemie-international edition, 2023)
Recently, chiral and nonplanar cutouts of graphene have been the favorites due to their unique optical, electronic, and redox properties and high solubility compared with their planar counterparts. Despite the remarkable progress in helicenes, pi-extended heterohelicenes have not been widely explored. As an anode in a lithium-ion battery, the racemic mixture of pi-extended double heterohelical nanographene containing thienothiophene core exhibited a high lithium storage capability, attaining a specific capacity of 424 mAh g-1 at 0.1 A g-1 with excellent rate capability and superior long-term cycling performance over 6000 cycles with negligible fade. As a first report, the pi-extended helicene isomer (PP and MM), with the more interlayer distance that helps faster diffusion of ions, has exhibited a high capacity of 300 mAh g-1 at 2 A g-1 with long-term cycling performance over 1500 cycles compared to the less performing MP and PM isomer and racemic mixture (150 mAh g-1 at 2 A g-1). As supported by single-crystal X-ray analysis, a unique molecular design of nanographenes with a fixed (helical) molecular geometry, avoiding restacking of the layers, renders better performance as an anode in lithium-ion batteries. Interestingly, the recycled nanographene anode material displayed comparable performance. A pi-extended double heterohelical nanographene of thienothiophene core fused with two hexabenzocoronene units exhibits excellent performance as an anode in a lithium-ion battery. The isomer (PP and MM) with more interlayer distance exhibited a high lithium storage capability compared to the other isomer and racemic mixture. Helical nanographene anodes display excellent rate capability, superior long-term cycling performance, and recyclability.image
Keywords: Battery; graphene; Li-ion battery; nanographene; Organic Electrode Material

Thermally activated delayed fluorescent solvent-free organic liquid hybrids for tunable emission applications - Nidhankar, Aakash D. D.; Goudappagouda; Kothavade, Premkumar D.; Dongre, Sangram D.; Veer, Sairam Dnyaneshwar; Dash, Soumya Ranjan; Rajeev, Kavya; Unni, K. N. Narayanan; Shanmuganathan, Kadhiravan; Babu, Sukumaran Santhosh (Chemistry-An Asian Journal, 2023)
The synthetic feasibility and excellent luminescence features of organic molecules attracted much attention and were eventually found useful in lighting applications. In this context, a solvent-free organic liquid having attractive thermally activated delayed fluorescence features in bulk along with high processability has prime importance. Herein, we report a series of naphthalene monoimide-based solvent-free organic liquids exhibiting cyan to red thermally activated delayed fluorescence with luminescence quantum yields up to 80% and lifetimes between 10 to 45 mu s. An effective approach explored energy transfer between liquid donors with various emitters exhibiting tunable emission colors, including white. The high processability of liquid emitters improved the compatibility with polylactic acid and was used for developing multicolor emissive objects using 3D printing. Our demonstration of the thermally activated delayed fluorescence liquid will be much appreciated as a processable alternate emissive material suitable for large-area lighting, display, and related applications.
Keywords: 3D printing; Energy Transfer; OLED; Organic Liquids; TADF

Boron- and oxygen-doped π-extended helical nanographene with circularly polarised thermally activated delayed fluorescence - Venugopal, Geethu; Kumar, Viksit; Jadhav, Ashok Badrinarayan; Dongre, Sangram D.; Khan, Abujunaid; Gonnade, Rajesh; Kumar, Jatish; Santhosh Babu, Sukumaran (Chemistry-A European Journal, 2024)
Helical nanographenes have garnered substantial attention owing to their finely adjustable optical and semiconducting properties. The strategic integration of both helicity and heteroatoms into the nanographene structure, facilitated by a boron-oxygen-based multiple resonance (MR) thermally activated delayed fluorescence (TADF), elevates its photophysical and chiroptical features. This signifies the introduction of an elegant category of helical nanographene that combines optical (TADF) and chiroptical (CPL) features. In this direction, we report the synthesis, optical, and chiroptical properties of boron, oxygen-doped pi-extended helical nanographene. The pi-extension induces distortion in the DOBNA-incorporated nanographene, endowing a pair of helicenes, (P)-B2NG, and (M)-B2NG exhibiting circularly polarized luminescence with glum of -2.3x10-3 and +2.5x10-3, respectively. B2NG exhibited MR-TADF with a lifetime below 5 mu s, and a reasonably high fluorescence quantum yield (50 %). Our molecular design enriches the optical and chiroptical properties of nanographenes and opens up new opportunities in multidisciplinary fields. B, O-doped pi-extended helical nanographene has been explored for its optical and chiroptical properties. The presence of helical and nanographene segments stabilize the helicity and imparts tunable optical properties. Helical nanographene display circularly polarized thermally activated delayed fluorescence. image
Keywords: circularly polarized luminescence; DOBNA; dual emission; nanographene; TADF

Tailoring helical ends of π-extended [6]heterohelicenes to control optical, and electrochemical features - Kumar, Viksit; Dongre, Sangram D.; Venugopal, Geethu; Narayanan, Aswini; Babu, Sukumaran Santhosh (Chemical Communications, 2024)
The inherent helical chirality and improved pi-stacking capabilities endow helicenes with fascinating photophysical characteristics when decorated with lateral pi-extensions. Here, we report the synthesis and physicochemical characterization of expanded hetero[6]helicenes fused with thiadiazole and selenadiazole rings at the helical ends. Comparing these heterohelicenes revealed the impact of the heteroatom-embedded aromatic rings on the excited state and redox features. A small structural variation of the terminal rings from thiadiazole to selenadiazole caused a striking change in the heterohelical nanographenes. The inherent helical chirality and improved pi-stacking capabilities endow helicenes with fascinating photophysical characteristics when decorated with heteroatoms.

Accessing electron-deficient π-extended pyrenes via non-K-region fusion - Dongre, Sangram D.; Kumar, Viksit; Kumar, Ravi; Babu, Sukumaran Santhosh (ORGANIC LETTERS, 2025)
This study presents a new class of pyrene derivatives featuring non-K-region fusion and electron-deficient pi-extension. By strategically introducing electron-withdrawing groups at the non-K positions, the optical and redox properties of these compounds were significantly altered. For the first time, we report a non-K-region fused acceptor pyrene with an extended pi-skeleton. The detailed characterizations revealed pronounced shifts in both absorption and emission spectra, accompanied by a significant lowering of the LUMO energy levels. Our results highlight non-K region-fused pyrenes as a promising building block for next-generation organic semiconductors with tunable electronic properties.

(Chiro)optical Properties of π-Extended Spiro-Double Carbo[7]helicene - Kumar, Viksit; Dongre, Sangram D.; Vandhanam, Aparna; Jadhav, Ashok Badrinarayan; Kumar, Jatish; Babu, Sukumaran Santhosh (Journal of Physical Chemistry Letters, 2025)
Helical nanographenes are a fascinating class of pi-extended chiral nanocarbons, where structural helicity imparts intrinsic chirality and unique optoelectronic properties to the rigid carbon framework. In this work, we synthesized a hexa-peri-hexabenzocoronene-based pi-extended spiro-double carbo[7]helicene. The helical distortion of the structure was unambiguously confirmed by X-ray crystallography. The optical properties were explored through UV-Vis absorption, fluorescence, and phosphorescence measurements, complemented by density functional theory (DFT) calculations. Remarkably, the pi-extended spiro-double carbo[7]helicene exhibited thermally activated delayed fluorescence (TADF) at room temperature and phosphorescence at low temperatures. Chiral HPLC successfully resolved the enantiomers into three fractions: (PP), (MM), and the meso forms (PM)/(MP), and chiroptical studies of the pure enantiomers revealed a moderately high g lum value of 1.58 x 10-3. Finally, the origin of the observed dissymmetry factors was rationalized by analyzing the transition electric dipole moments (TEDM) and transition magnetic dipole moments (TMDM) derived from time-dependent density functional theory (TD-DFT) calculations.

Chiroptical amplification of [7]-helicene nanographene by additional helical chirality - Dongre, Sangram D.; Venugopal, Geethu; Kumar, Viksit; Badrinarayan Jadhav, Ashok; Kumar, Jatish; Babu, Sukumaran Santhosh (Angewandte Chemie-International Edition, 2025)
Nanographenes have captivated scientific interest since the pioneering discovery of graphene. Recently, attention has shifted towards exploring chiral and nonplanar nanographenes, for their distinct optical, chiroptical, and electronic properties. Despite the growing acceptance of helicenes, the research on inducing helical chirality on pi-extended derivatives to boost chiroptical properties remains unattended. In our study, we introduce a new pi-extended [7]-helicene resulting from the condensation of diamines with 3,6-dibromophenanthrene-9,10-dione, complemented by two hexabenzocoronene arms in the periphery. Notably, the nanographene containing binaphtho-[1,4]diazocine, compared to the corresponding phenazine, exhibits a remarkable average 2.5, 5, and 10-fold enhancements in quantum yield, dissymmetry factor, and brightness, respectively, when measured in five different solvents. These improvements underscore the significance of the induced helical chirality by the antiaromatic binaphtho-[1,4]diazocine in influencing the chiroptical properties of the helical nanographene. Our research represents a significant stride toward unlocking the potential of pi-extended helicenes and lays the groundwork for further exploration in designing and synthesizing new chiral nanomaterials.
Keywords: circularly polarised luminescence; dissymmetry factor; helicene; nanographene; quantum yield

Regioisomeric π-extended nanographene with long-lived phosphorescence afterglow - Kumar, Viksit; Venugopal, Geethu; Jadhav, Ashok Badrinarayan; Dongre, Sangram D.; Gonnade, Rajesh; Kumar, Jatish; Ruer, Paul C.; Hupp, Benjamin; Steffen, Andreas; Babu, Sukumaran Santhosh (Angewandte Chemie-International Edition, 2025)
The cutouts of graphene sheets, particularly those with a nonplanar topology, present vast opportunities for advancement. Even a slight deviation from the planar structure can lead to intriguing (chiro)optical features for helically twisted nanographenes. In this context, we introduce two regioisomeric pi-extended nanographenes that exhibit distinct excited-state characteristics. The helicene structure and the photophysical features can be easily tuned by changing the connecting position of the nanographene to the carbazole core (2,7- and 3,6-). Single-crystal X-ray diffraction analysis confirmed the formation of nanographenes with bent and helical conformations. Both derivatives exhibited thermally activated delayed fluorescence at room temperature and phosphorescence at low temperatures. Notably, the nanographene with the bent structure displayed an impressive red afterglow lasting over 30seconds, in contrast to the very weak afterglow observed in the helical structure. DFT calculations revealed the existence of an isoenergetic higher triplet state (T-8) and comparatively weak spin-orbit coupling (T-1-S-0), thereby enabling the bent nanographene to exhibit a long-lived component and strong afterglow. Our findings highlight the significance of regioisomeric nanographenes with exceptional optical properties and offer a deeper understanding of the structure-property relationship in nonplanar nanographenes.
Keywords: Afterglow; CPL; Helicenes; nanographene; Phosphorescence; TADF